Consumer Responses to Regional Preferences and Customer Service in the Property Industry: Evidence from Bekasi City - Raden Tumenggung Handriyantho Hadipuro (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how regional preferences and customer service influence consumer behavior in the property industry in Bekasi City. Using a quantitative explanatory design, data from 212 respondents were analyzed using PLS-SEM with SmartPLS 4. Results show that regional preferences and customer service significantly influence purchase decisions and consumer satisfaction. Perceived value does not significantly influence purchase decisions, but significantly affects consumer satisfaction. Satisfaction significantly mediates loyalty formation, while perceived value does not mediate purchase decisions. Findings indicate that property consumer behavior follows a partial and non-linear mediation process in high-involvement purchase decisions.